2018
DOI: 10.1016/j.eurpsy.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Who are the European youths willing to engage in radicalisation? A multidisciplinary review of their psychological and social profiles

Abstract: There are many similarities between psychopathological manifestations of adolescence and mechanisms at stake during the radicalisation process. As a consequence, and despite the rarity of psychotic disorders, mental health professionals have a role to play in the treatment and understanding of radical engagement among European youth. Studies with empirical data are limited, and more research should be promoted (in particular in females and in non-Muslim communities) to better understand the phenomenon and to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
79
2
18

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 54 publications
4
79
2
18
Order By: Relevance
“…Recent studies have revealed various socio-environmental and neurobiological factors associated with terrorist behaviour (Box 2).
Socio-environmental and neurobiological factors associated with terrorist behaviour Socio-environmental factors Socio-environmental risk factors that predispose a person to terrorism include (Campelo 2018): family dysfunctionfriendships with radicalised individualsunstable geopolitical environmentsocietal polarisation (unequal socio-economic conditions in the country) Neurobiological factors Violent offenders were found to have the following (Bogerts 2018): decreased grey matter in the orbitofrontal and prefrontal cortexdecreased volume of all temporolimbic structures and the posterior cingulate cortexreduced functional connectivity between the frontal cortex and the limbic areas, anterior insula and posterior cingulate cortexStructural and functional deficits in brain regions crucial for empathy and compassion, similar to those in individuals with antisocial personality disorder, have also been found (Blair 2005; Marazziti 2013).
…”
Section: Socio-environmental and Neurobiological Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have revealed various socio-environmental and neurobiological factors associated with terrorist behaviour (Box 2).
Socio-environmental and neurobiological factors associated with terrorist behaviour Socio-environmental factors Socio-environmental risk factors that predispose a person to terrorism include (Campelo 2018): family dysfunctionfriendships with radicalised individualsunstable geopolitical environmentsocietal polarisation (unequal socio-economic conditions in the country) Neurobiological factors Violent offenders were found to have the following (Bogerts 2018): decreased grey matter in the orbitofrontal and prefrontal cortexdecreased volume of all temporolimbic structures and the posterior cingulate cortexreduced functional connectivity between the frontal cortex and the limbic areas, anterior insula and posterior cingulate cortexStructural and functional deficits in brain regions crucial for empathy and compassion, similar to those in individuals with antisocial personality disorder, have also been found (Blair 2005; Marazziti 2013).
…”
Section: Socio-environmental and Neurobiological Factorsmentioning
confidence: 99%
“…A meta-analysis of 22 studies of radicalised European youths by Campelo et al (2018) yielded a proposed model for identifying risk factors of ‘radicalisation’ among European adolescents and young adults. The suggested socio-environmental risk factors included: family dysfunction, friendships with radicalised individuals, unstable geopolitical environment, and societal polarisation (unequal socio-economic conditions in the country).…”
Section: Socio-environmental and Neurobiological Factorsmentioning
confidence: 99%
“…In general, the above conclusion is confirmed by the trends of mass consciousness and behavior that do not outrun the "red lines" of the legitimacy of power and the lack of catastrophic consciousness. However, youth extremism as a behavioral model aimed at the conflict of youth and society, the clash of interests and needs of various social groups under the marker of disorder and discrimination of youth, its readiness for open conflict and violence against the state is manifested not only eventfully, but also acquires some regularity on the basis of the growth of extremist sentiments of young people in socially significant and alarming aspects of public life [2]. Therefore, the wave-like nature of youth extremism, the alternation of recessions and booms contains an important problem for Russian society, related to the neutralization of the risks of youth extremism, and the integration of young people in various fields of social life, especially in socio-political one.…”
Section: Ductionmentioning
confidence: 99%
“…Dat is tussen doornen naar druiven zoeken. Nederigheid heelt wonden, arrogantie verergert ze' (Gandhi, 2017). Deze les in preventie kan mogelijk door de GGZ, wijkteams, welzijnsorganisaties, politie, veiligheidskundigen en lokale gemeentepolitici worden omarmd bij de aanpak van radicaliseren en terrorisme door gemeenten (steden en dorpen).…”
unclassified
“…In deze vragenlijst zijn onder meer vragen opgenomen over het oordeel van de ondervraagden over Engelse troepen die zijn afgereisd naar Irak en Afghanistan en verder een oordeel over het tegen deze troepen vechten. In de vierde plaats een review over Europese jongeren waaruit blijkt dat de psychopathologische uitingen bij adolescenten vele gelijkenissen vertonen met mechanismen gedurende het proces van radicaliseren (Campelo et al, 2018). De oproep van Mahatma Gandhi tot nederigheid en het onderhavige betoog nopen tot een herziening van de preventielessen die worden uitgedragen door instanties die binnen de context van Nederlandse gemeenten zich inzetten voor de aanpak van radicaliseren en terrorisme.…”
unclassified